Placental deposition of C-reactive protein is a common feature of human pregnancy. Issue 6 (June 2015) - Kim, E.N.; Yoon, B.H.; Jeon, E.J.; Lee, J.B.; Hong, J.-S.; Lee, J.Y.; Hwang, D.; Kim, K.C.; Kim, J.-S.; Kim, C.J.
Abstract: This study examined the occurrence of placental C-reactive protein (CRP) in normal pregnancy with term delivery, spontaneous preterm delivery (sPTD), preeclampsia, and miscarriage. CRP immunoreactivity was detected in the syncytiotrophoblast. The immunopositive rate was significantly higher in sPTD than preeclampsia. The CRP immunopositive rate was also higher in acute chorioamnionitis than those without and showed a good correlation with the maternal serum CRP concentration. CRP mRNA expression was not detected in human and mouse placentas or choriocarcinoma cells. CRP may play a role in the pathological and physiological states of pregnancy. Highlights: We investigated CRP immunoreactivity in human placentas. CRP positivity is lower in preeclampsia with FGR than in sPTD or preeclampsia. CRP immunopositivity is positively associated with acute chorioamnionitis. CRP immunopositivity is inversely associated with maternal vascular underperfusion. Placental CRP immunoreactivity mirrors maternal serum CRP concentration.